Pneumomediastinum following endobronchial ultrasound and transbronchial needle aspirate (EBUS-TBNA) sampling of mediastinal lymph nodes. Issue 8 (2nd August 2021) - Stanton, Alice; Conroy, Kevin; Miller, Graham
Abstract : A 72-year-old female patient underwent endobronchial ultrasound and transbronchial needle aspirate sampling of mediastinal lymph nodes to investigate a middle lobe abnormality following an urgent referral. CT imaging completed the following day demonstrated a pneumomediastinum. At clinical review, the patient remained clinically stable and no intervention was required.